2021
DOI: 10.15766/mep_2374-8265.11080
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the Evaluation of Female Pelvic Pain: A Hands-On Simulation to Reinforce Exam Skills and Introduce Transvaginal Ultrasound

Abstract: Introduction: Reproductive-age female patients commonly seek evaluation for pelvic pain in a variety of health care settings. Thus, teaching medical students how to effectively evaluate female pelvic pain is a necessary part of medical education. There are limited opportunities, however, to reinforce the needed skills for this common but sensitive presentation that can be anxiety-producing for preclinical students. Methods: The case involved a 23-year-old female presenting with lower abdominal/pelvic pain. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Another study of 15 doctors, showed improved confidence, more systematic approach and documentation [16] but also limited perceptions to questionnaire analysis. A similar study reported questionnaire responses from 28 participants following a four hour TVUS simulation course, showing that participants believed that simulation training applied to clinical practice and that their performance would improve after simulation training [15]; a final study of medical students showed enhanced clarity and knowledge following TVUS simulation training [17].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Another study of 15 doctors, showed improved confidence, more systematic approach and documentation [16] but also limited perceptions to questionnaire analysis. A similar study reported questionnaire responses from 28 participants following a four hour TVUS simulation course, showing that participants believed that simulation training applied to clinical practice and that their performance would improve after simulation training [15]; a final study of medical students showed enhanced clarity and knowledge following TVUS simulation training [17].…”
Section: Discussionmentioning
confidence: 92%
“…Previous work has further focused on the effect of trainee preconceived bias of simulation education and shown that it can limit the benefits of simulation [17]. If trainees see simulation as only a re-creation of life events, then their learning may be stunted; in comparison those that saw beyond a method for practicing basic skill can grasp the additional educational opportunities that simulation afforded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Goldsworthy et al [ 41 ] found that virtual auscultation using authentic real patient sounds (rather than synthetically derived sounds used by past interventions), had improved performance in nursing students’ competence in detecting cardiac murmurs. Pearson et al [ 49 ] explored the implementation of simulation to provide a comprehensive basis for the learning of female pelvic examination that combined touch-based examination and transvaginal ultrasound. These high-fidelity simulations were shown to assist students to develop these physical examination skills that combined touch and ultrasound, and these skills were transferable to clinical encounters [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pearson et al [ 49 ] explored the implementation of simulation to provide a comprehensive basis for the learning of female pelvic examination that combined touch-based examination and transvaginal ultrasound. These high-fidelity simulations were shown to assist students to develop these physical examination skills that combined touch and ultrasound, and these skills were transferable to clinical encounters [ 49 ].…”
Section: Resultsmentioning
confidence: 99%